RSPO3 is important for trabecular bone and fracture risk in mice and humans - Karin H. Nilsson (Nature Portfolio, 2021)
Genetic association signals for fractures have been reported at the RSPO3 locus, but the causal gene and the underlying mechanism are unknown. Here, the authors show that RSPO3 exerts an important role for vertebral trabecular bone mass and bone strength in mice and fracture risk in humans.